Experimental and numerical investigation of sebacic acid/expanded graphite composite phase change material in a double-spiral coiled heat exchanger. (December 2020) - Lin, Wenzhu; Ling, Ziye; Zhang, Zhengguo; Fang, Xiaoming
Highlights: The thermal performance of sebacic acid /expanded graphite composite material in a double-spiral coiled heat exchanger was studied. Experimental and numerical tests about charging performance were presented. The inlet temperature, flow rate as well as thermal conductivity of phase change material were investigated. Abstract: Solar energy is considered to be one of the most prospective sources of energy, but it needs suitable energy storage technology for efficient usage. Among various applications of thermal energy storage of solar heating, the medium-high temperature (over 120 °C) heat accumulation has a greater market potential since energy with higher temperature has higher quality. The medium-high temperature solar energy utilization has wide application prospect, including building heating system, solar water heaters, et al. This work studies the thermal energy storage performance and phase change behavior of sebacic acid (SA)/expanded graphite (EG) composite material in a double-spiral coiled heat exchanger, while the heat transfer oil works as thermal fluid concerning with high temperature of system. SA is a promising phase change material to store medium-high temperature thermal energy. Results show that the system with SA/EG composite has uniform temperature distribution inside the energy storage tank. The effect of the flow rate and inlet temperature of heat transfer fluid on charging efficiency is explored. The numerical method is adopted to further study the thermal conductivity of SA/EG and the thermal performance of system.